Skeletal muscle feature of different populations in large yellow croaker (Larimichthys crocea): from an epigenetic point of view - Xie, Shangwei; Jiang, Lihua; Song, Weihua; Zheng, Jialang; Liu, Yifan; Chen, Shun; Yan, Xiaojun (Frontiers in Molecular Biosciences, 2024)
Fish skeletal muscle is composed of well-defined fiber types. In order to identify potential candidate genes affecting muscle growth and development under epigenetic regulation. Bisulfite sequencing was utilized to analyze and compare the muscle DNA methylation profiles of Larimichthys crocea inhabiting different environments. The results revealed that DNA methylation in L. crocea was predominantly CG methylation, with 2396 differentially methylated regions (DMRs) identified through comparisons among different populations. The largest difference in methylation was observed between the ZhouShan and JinMen wild populations, suggesting that L.crocea may have undergone selection and domestication. Additionally, GO and KEGG enrichment analysis of differentially methylated genes (DMGs) revealed 626 enriched GO functional categories, including various muscle-related genes such as myh10, myf5, myf6, ndufv1, klhl31, map3k4, syn2b, sostdc1a, bag4, and hsp90ab. However, significant enrichment in KEGG pathways was observed only in the JinMen and XiangShan populations of L. crocea. Therefore, this study provides a theoretical foundation for a better understanding of the epigenetic regulation of skeletal muscle growth and development in L. crocea under different environmental conditions.